ANALISIS VEGETASI GULMA PADI PANDANWANGI (Oryza sativa L. Aromatic) DI SENTRA PENANAMAN PADI PANDANWANGI KABUPATEN CIANJUR - Widya Sari; Marwan Azis (Fakultas Sains Terapan Universitas Suryakancana, 2021)
Pandanwangi rice is superior varieties in Cianjur which has special geographical indication. Weed is one of the causes in declining of Pandanwangi rice production. The purpose of this research were to know the index of weed abundance, weed diversity index and weed similarity index on Pandanwangi rice plantation. This research was carried out from December until June 2018. with observation methods.The results of this research showed that there were differences in the abundance index (Di) of broad and narrow leaves weed in four sub-districts of Pandanwangi rice cultivation center. Cianjur subdistrict had a higher value of abundance index of broad leaf weeds and narrow leaf weeds than other districts, there was no differences of broad leaf weed and narrow leaf weeds diversity index in four sub-districts of Pandanwangi rice cultivation center. Weed diversity values were low(H '<1)', with H 'values of broad leaf weeds and narrow leaf weeds were 0.21 -0.39 and there were no differences of broad leaf weed and narrow leaf weeds similarity index in four sub-districts Index, the values were very low, wide leaf Is = 0.04 and the narrowleaf Is = 0.00. Many or at least the types of weeds contained in a land are affected by the quality of the environment and the type of species because each type of weed has different adaptations and tolerances to its habitat.